PERAN PEMBIAYAAN QARDL DALAM MENINGKATKAN PENDAPATAN USAHA KECIL MENENGAH (UKM) PADA ANGGOTA BMT MANDIRI SEJAHTERA CABANG DUKUN GRESIK - Reni Wulan Sari; Khozainul Ulum (Akademika, 2021)
Financial institutions act as financial intermediary institutions. The activities of an activity agency can be in the form of raising funds by offering various schemes, channeling funds with various schemes or conducting activities to raise funds and channel funds at once. Such as LKS, BUS, UUS, AS, UPS, and BMT. BMT as a business institution that further delevops its business in the financial sector, namely savings and loans. BMT’s product saving product include saving, time deposits, while loan products include financing, BMT financing, mudlarabah financing, musyarakah financing, murabahah financing, qardl financing, and qardl al-hasan financing. This research is a qualitative research aimed to answer questions about how the role of qard contract financing in BMT Mandiri Sejahtera Branch Dukun Gresik, as well as how to analyze the role of qard financing in raising the income of small and medium enterprises (UKM) to members in BMT Mandiri Sejahtera Branch Dukun Gresik. This research method using qualitative approach. Sources of data obtained from interviews, documentation, observation. Data analysis used qualitative data analysis that was inductive with descriptive approach. The results show the role of qardl contract financing in increasing the income of small and medium enterprises (UKM) to members in BMT Mandiri Sejahtera Branch Dukun Gresik. The definition of qardl financing in BMT Mandiri Sejahtera Branch of Dukun Gresik is, the provision of this financing is for small and medium business traders (UKM) who have stalls in the shaman gresik market and increase capital for small and medium enterprises (UKM). From the interviews and observation shows that there is an increase in the efforts of members who after obtaining the financing akad qardl.